Islamic Capital Market Reactions to Political Transition: Evidence from Indonesia's 2024 Presidential Election - Suhadi, Suhadi; Maharany, Indah Dewi (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study conducts an event analysis on the impact of the official announcement of the 2024 Indonesian presidential election results by the General Elections Commission (KPU) on stock market performance. The objective is to investigate changes in abnormal returns (AR) and trading volume activity (TVA) during an 11-day event window (±5 days surrounding the announcement date) and a 60-day estimation period. The sample comprises 30 companies listed on the Jakarta Islamic Index (JII), representing nine industry sectors, selected through saturated sampling. Analytical methods include the Paired T-test and the Wilcoxon Signed Rank Test to examine statistical differences in AR and TVA before and after the event. The findings reveal no significant difference in AR for the JII overall, although the consumer non-cyclicals sector displays a noteworthy deviation. In contrast, a significant change in TVA is observed, particularly within the basic materials sector. These results underscore the importance for investors in the Islamic capital market to remain attentive to political developments that may affect asset performance. The study provides meaningful insights for investors, regulators, and academics regarding portfolio diversification and risk management in the context of political uncertainty, contributing to the broader discourse on Islamic capital markets. Abstrak Reaksi Pasar Modal Syariah terhadap Transisi Politik: Studi Kasus Pemilihan Presiden Indonesia 2024. Penelitian ini menganalisis dampak pengumuman resmi hasil Pemilu Presiden 2024 oleh Komisi Pemilihan Umum (KPU) terhadap kinerja pasar saham, khususnya pada indeks saham syariah. Tujuannya adalah untuk mengetahui perubahan return tidak normal (abnormal return/AR) dan aktivitas volume perdagangan (TVA) selama periode peristiwa selama 11 hari (5 hari sebelum dan sesudah pengumuman), serta periode estimasi selama 60 hari. Sampel penelitian terdiri dari 30 perusahaan dalam Jakarta Islamic Index (JII) dari 9 sektor industri, menggunakan metode sampling jenuh. Pengujian dilakukan dengan uji Paired T-test dan Wilcoxon Signed Rank Test. Hasilnya menunjukkan tidak ada perbedaan signifikan dalam AR secara keseluruhan pada indeks JII, namun terdapat perbedaan signifikan pada sektor konsumer non-siklikal. Sementara itu, terdapat perubahan signifikan pada TVA, khususnya di sektor bahan dasar (basic materials). Temuan ini menegaskan pentingnya kewaspadaan investor di pasar saham syariah terhadap dinamika politik yang dapat mempengaruhi portofolio. Penelitian ini memberikan wawasan bagi investor, regulator, dan akademisi terkait strategi diversifikasi dan manajemen risiko dalam menghadapi ketidakpastian politik, serta memperkaya kajian literatur tentang pasar modal syariah